Survival outcomes of hepatic resection compared with transarterial chemoembolization or sorafenib for hepatocellular carcinoma with portal vein tumor thrombosis - Jung Min Lee (Clinical and Molecular Hepatology, 2016)
Background/Aims:Treating hepatocellular carcinoma (HCC) with portal vein tumor thrombosis (PVTT) remains controversial. We compared the outcomes of hepatic resection (HR), transarterial chemoembolization (TACE), and sorafenib therapy as treatments for HCC with PVTT. Methods:Patients diagnosed as HCC with PVTT between January 2000 and December 2011 who received treatment with sorafenib, HR, or TACE were included. Patients with main PVTT, superior mesenteric vein tumor thrombosis, or Child-Turcotte-Pugh (CTP) class C were excluded. The records of 172 patients were analyzed retrospectively. HR, TACE, and sorafenib treatment were performed is 40, 80, and 52 patients respectively. PVTT was classified as either involving the segmental branch (type I) or extending to involve the right or left portal vein (type II). Results:The median survival time was significantly longer in the HR group (19.9 months) than in the TACE and sorafenib groups (6.6 and 6.2 months, respectively; both p<0.001), and did not differ significantly between the latter two groups (p=0.698). Among patients with CTP class A, type I PVTT or unilobar-involved HCC, the median survival time was longer in the HR group than in the TACE and sorafenib groups (p=0.006). In univariate analyses, the initial treatment method, tumor size, PVTT type, involved lobe, CTP class, and presence of cirrhosis or ascites were correlated with overall survival. The significant prognostic factors for overall survival in Cox proportional-hazards regression analysis were initial treatment method (HR vs. TACE: hazard ratio=1.750, p=0.036; HR vs. sorafenib: hazard ratio=2.262, p=0.006), involved lobe (hazard ratio=1.705, p=0.008), PVTT type (hazard ratio=1.617, p=0.013), and CTP class (hazard ratio=1.712, p=0.012). Conclusions:Compared with TACE or sorafenib, HR may prolong the survival of patients with HCC in cases of CTP class A, type I PVTT or unilobar-involved HCC.